Stable isotopic evidence for the excess leaching of unprocessed atmospheric nitrate from forested catchments under high nitrogen saturation - W. Ding; U. Tsunogai; F. Nakagawa; T. Sambuichi; M. Chiwa; T. Kasahara; K. Shinozuka (Biogeosciences, 2023)
Owing to the elevated loading of nitrogen through atmospheric deposition, some forested ecosystems become nitrogen saturated, from which elevated levels of nitrate are exported. The average concentration of stream nitrate eluted from upstream and downstream of the Kasuya Research forested catchments (FK1 and FK2 catchments) in Japan were more than 90 µM, implying that these forested catchments were under nitrogen saturation. To verify that these forested catchments were under the nitrogen saturation, we determined the export flux of unprocessed atmospheric nitrate relative to the entire deposition flux (Matm<mspace linebreak="nobreak" width="0.125em"/>/<mspace linebreak="nobreak" width="0.125em"/>Datm<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="55pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="8e423e23c6ab67d52cbd4ec036c5238a"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-20-753-2023-ie00001.svg" width="55pt" height="14pt" src="bg-20-753-2023-ie00001.png"/></svg:svg> ratio) in these catchments; because the Matm<mspace width="0.125em" linebreak="nobreak"/>/<mspace width="0.125em" linebreak="nobreak"/>Datm<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="55pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="7c28d595bb2ff4c210ff97d527fad3a1"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-20-753-2023-ie00002.svg" width="55pt" height="14pt" src="bg-20-753-2023-ie00002.png"/></svg:svg> ratio has recently been proposed as a reliable index to evaluate nitrogen saturation in forested catchments. Specifically, we determined the temporal variation in the concentrations and stable isotopic compositions, including Δ17O, of stream nitrate in the FK catchments for more than 2 years. In addition, for comparison, the same parameters were also monitored in the Shiiba Research forested catchment (MY catchment) in Japan during the same period, where the average stream nitrate concentration was low, less than 10 µM. While showing the average nitrate concentrations of 109.5, 90.9, and 7.3 µM in FK1, FK2, and MY, respectively, the catchments showed average Δ17O values of +2.6 ‰, +1.5 ‰, and +0.6 ‰ in FK1, FK2, and MY, respectively. Thus, the average concentration of unprocessed atmospheric nitrate ([NO<msubsup>3-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="9pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="fa1148a5a7ab62133104fb46bf612014"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-20-753-2023-ie00003.svg" width="9pt" height="16pt" src="bg-20-753-2023-ie00003.png"/></svg:svg>atm]) was estimated to be 10.8, 5.1, and 0.2 µM in FK1, FK2, and MY, respectively, and the Matm<mspace width="0.125em" linebreak="nobreak"/>/<mspace linebreak="nobreak" width="0.125em"/>Datm<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="55pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="4a6a9dc2d2275e1982bdebfbff3b4a68"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-20-753-2023-ie00004.svg" width="55pt" height="14pt" src="bg-20-753-2023-ie00004.png"/></svg:svg> ratio was estimated to be 14.1 %, 6.6 %, and 1.3 % in FK1, FK2, and MY, respectively. The estimated Matm<mspace width="0.125em" linebreak="nobreak"/>/<mspace width="0.125em" linebreak="nobreak"/>Datm<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="55pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="f231cdb2121923e0c11bfd66a425c766"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-20-753-2023-ie00005.svg" width="55pt" height="14pt" src="bg-20-753-2023-ie00005.png"/></svg:svg> ratio in FK1 (14.1 %) was the highest ever reported from temperate forested catchments monitored for more than 1 year. Thus, we concluded that nitrogen saturation was responsible for the enrichment of stream nitrate in the FK catchments, together with the elevated NO<msubsup>3-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="9pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="06954914259a113e7faaa0d01a8ee756"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-20-753-2023-ie00006.svg" width="9pt" height="16pt" src="bg-20-753-2023-ie00006.png"/></svg:svg>atm leaching from the catchments. While the stream nitrate concentration ([NO<msubsup>3-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="9pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="2a83a52cafded6cc529076279999d0cd"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-20-753-2023-ie00007.svg" width="9pt" height="16pt" src="bg-20-753-2023-ie00007.png"/></svg:svg>]) can be affected by the amount of precipitation, the Matm<mspace width="0.125em" linebreak="nobreak"/>/<mspace linebreak="nobreak" width="0.125em"/>Datm<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="55pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="9dff41ca5c5e9de6e3bab45660a04458"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-20-753-2023-ie00008.svg" width="55pt" height="14pt" src="bg-20-753-2023-ie00008.png"/></svg:svg> ratio is independent of the amount of precipitation; thus, the Matm<mspace width="0.125em" linebreak="nobreak"/>/<mspace width="0.125em" linebreak="nobreak"/>Datm<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="55pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="a7770c59c3732e6ee31c7ce94c02f6e1"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-20-753-2023-ie00009.svg" width="55pt" height="14pt" src="bg-20-753-2023-ie00009.png"/></svg:svg> ratio can be used as a robust index for evaluating nitrogen saturation in forested catchments.